A Green Synthesis of Substituted Coumarins Using Nano Graphene Oxide as Recyclable Catalyst. Issue 5 (17th April 2015) - Khodabakhshi, Saeed; Marahel, Farzaneh; Rashidi, Alimorad; Abbasabadi, Masoud Khaleghi
Abstract One‐pot synthesis of some pyranocoumarins and biscoumarins using graphene oxide nanosheets as efficient catalyst has been investigated. The green methods offer appealing attributes such as excellent yields, short reactions times, use of a safe and recyclable catalyst, and a simple workup procedure.